1998
DOI: 10.1046/j.1365-313x.1998.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of a novel annexin‐like protein encoded by a stress and abscisic acid responsive gene in alfalfa

Abstract: SummaryWe report here on the isolation and characterization of a full-length cDNA clone from alfalfa termed AnnMs2 encoding a 333 amino acid long polypeptide that shows 32-37% sequence identity with both mammalian and plant annexins, and has four tandem repeats. While other plant annexins exhibit a high level of sequence similarity to each other (up to 77% identity at amino acid level), AnnMs2 appears to be a distinct type of plant annexins. All the four endonexin folds contain the conserved eukaryotic motif w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 61 publications
4
68
0
2
Order By: Relevance
“…Many nuclear proteins can also be found in the cytosol (Yoneda 2000), and the translocation of proteins into and out of the nucleus can be employed by cells to regulate of the activity of such proteins. Induction of plant nuclear proteins by abiotic stresses has also been described previously (Godoy et al 1994;Kovacs et al 1998;Ascenzi & Gantt 1999;Munnik et al 1999;Castillo et al 2000;Scippa et al 2000). Not surprisingly, some of these proteins were also found localized both in the nucleus and cytosol (Godoy et al 1994;Houde et al 1995;Scippa et al 2000).…”
supporting
confidence: 76%
“…Many nuclear proteins can also be found in the cytosol (Yoneda 2000), and the translocation of proteins into and out of the nucleus can be employed by cells to regulate of the activity of such proteins. Induction of plant nuclear proteins by abiotic stresses has also been described previously (Godoy et al 1994;Kovacs et al 1998;Ascenzi & Gantt 1999;Munnik et al 1999;Castillo et al 2000;Scippa et al 2000). Not surprisingly, some of these proteins were also found localized both in the nucleus and cytosol (Godoy et al 1994;Houde et al 1995;Scippa et al 2000).…”
supporting
confidence: 76%
“…This is accompanied by up to two-fold changes in membrane surface area, accomplished by vesicle secretion and endocytosis (reviewed in Schroeder et al, 2001). Consistent with this, ABA induces expression of an annexin-like gene (Kovacs et al, 1998), requires syntaxin function for normal ion channel response (Leyman et al, 1999) and reorganization of the actin cytoskeleton to a randomly oriented pattern (Eun and Lee, 1997).…”
Section: Stomatal Regulationmentioning
confidence: 88%
“…In contrast to previous reports (Kovacs et al, 1998;Cantero et al, 2006), we tested for expression changes in fully expanded leaves of 6-to 8-week-old plants. We found that AnnAt1 mRNA levels were significantly elevated after virtually all applied treatments, reaching the highest level and being the most sustained after treatment with ABA and during drought (Fig.…”
Section: Expression Of Annat1 Is Up-regulated By a Variety Of Stress mentioning
confidence: 99%
“…One of the first reports indicating a role for annexin in stress responses documented the up-regulation of an alfalfa (Medicago sativa) annexin in response to osmotic stress, abscisic acid (ABA), and drought (Kovacs et al, 1998). Transcriptome studies in Arabidopsis (Arabidopsis thaliana) have also revealed changes in annexin gene expression in response to a variety of abiotic stresses (Kreps et al, 2002).…”
mentioning
confidence: 99%